Studi Populasi dan Habitat Ikan Semah (Tor sp.) di Sungai Napal Licin Kabupaten Merangin - Andriyanto (Pendidikan Biologi STKIP YPM Bangko, 2019)
The aim of this study was to determine the population abundance, species and habitat of semah fish in Napal Licin River, Merangin District, Jambi Province. This study was conducted in March 2019. Data collection was carried out using the Purposive Random Sampling method in four deliberately determined stations, there are Pulau Kemang, Beringin Sanggul, Bukit Punjung and Sakai. These stations are villages that located in the Napal Licin watershed. The fishs sample were caught using nets, then it were identified in the laboratory. Observation of the semah fish habitat was carried out directly. Water quality parameters ware measured in the site and laboratory. The results showed that population abundance of semah fish at the Napal Licin river was very low, the abundance in the station 1 was 0.03 ind /m2, station 3 was 0.06 ind /m2, whereas at stations 2 and 4 the abundance were 0, 00 ind/m2 because there are no semah fish found. The frequency of attendance category of semah fish at the Napal Licin river was very rare, at station 1 the frequency of attendance was 5.5%, station 3 was 11.1% while in station 2 and 4 the frequency of attendance were 0%. The Semah fish species that obtained only 1 species, Tor Tambroides. The degradation of semah fish habitat at the Napal Licin River was mainly caused by the illegal gold mining activities.